Model Pembelajaran Kooperatif Team Games Tournament pada Pembelajaran IPAS terhadap Partisipasi dan Hasil Belajar - Putu Lely Somya Prabawati; I Nyoman Jampel; I Ketut Suma (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study wants to know how the Team Games Tournament (TGT) cooperative learning method affects students' participation and learning outcomes in science lessons in grade IV of SD Gugus Tuanku Imam Bonjol. In this study, a control group design was used after treatment. For example, 59 students were randomly selected. The results showed that students who used TGT were more active and more successful than students who learned in the usual way. The results showed that students who used the TGT method were more active and more successful than students who learned in the usual way. This finding encourages the use of the TGT model in teaching science to make learning more effective. MANOVA analysis in this study revealed that: (1) The total F statistic was recorded at 0.999 with a significant value of 0.000. The fact that the value is smaller than 0.05 indicates that learning outcomes and participation are significantly impacted by the use of learning media. (2) Learning Outcomes has a significance value of 0.000. The null hypothesis (H0) is rejected because this result is likewise less than 0.05. H0 is rejected, indicating a significant difference in learning participation based on the TGT Learning Model treatment. This indicates that the TGT Learning Model teaching method clearly influences learning outcomes; (3) the significance value set for learning participation also displays the number 0.000, which is also less than 0.05.